2019
DOI: 10.1159/000502257
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and Aging: A Review

Abstract: Metformin is sometimes proposed to be an “anti-aging” drug, based on preclinical experiments with lower-order organisms and numerous retrospective data on beneficial health outcomes for type 2 diabetics. Large prospective, placebo-controlled trials are planned, in pilot stage or running, to find a new use (or indication) for an aging population. As one of the metformin trials has “frailty” as its endpoint, similar to a trial with a plant-derived senolytic, the latter class of novel anti-aging drugs is briefly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(74 citation statements)
references
References 97 publications
0
71
0
3
Order By: Relevance
“…Metformin, a widely prescribed first-line oral drug to treat type 2 diabetes, inhibits cellular senescence in vitro and in animal models via multiple molecular and cellular mechanisms [103][104][105]. For example, metformin inhibits oncogene-induced SASP by blocking nuclear factor-κB activation in human diploid fibroblasts [106].…”
Section: Adipocytesmentioning
confidence: 99%
“…Metformin, a widely prescribed first-line oral drug to treat type 2 diabetes, inhibits cellular senescence in vitro and in animal models via multiple molecular and cellular mechanisms [103][104][105]. For example, metformin inhibits oncogene-induced SASP by blocking nuclear factor-κB activation in human diploid fibroblasts [106].…”
Section: Adipocytesmentioning
confidence: 99%
“…Two crucial membrane compartments for the maintenance and regulation of endosomal acidic pH, are Vacuolar ATPase (V-ATPase) as proton pumping or acidifier compartment, and endosomal Na+/H+ exchangers (eNHEs) as proton leaking or alkalizing compartment on the endosomal membrane [5]. It is not crystal clear but several studies have suggested that Metformin can directly act on the eNHEs and/or the V-ATPase via its guanidine scaffold similar to Amiloride, then leads to the inhibition of viral infection through increasing the cellular pH and subsequently interfering with the endocytic cycle [5][6][7].…”
Section: To the Editormentioning
confidence: 99%
“…is an important mechanism for the glucose-lowering effect of metformin (Glossmann and Lutz, 2019). An immunometabolism-based beneficial effect of metformin may also contribute to the improved outcome in nondiabetic HF patients (Rena and Lang, 2018).…”
Section: Sglt2 Inhibitorsmentioning
confidence: 99%
“…Apart from its effect on diabetes and the heart, metformin treatment was shown to extend the lifespan in mice, highlighting a potential anti-aging effect of the drug (Martin-Montalvo et al, 2013). However, this effect was not found in other species (Glossmann and Lutz, 2019). Further results for a potential anti-aging effect of metformin may be expected from the Targeting Aging with Metformin (TAME) trial, which specifically investigates the effect of metformin on the onset of aging-related diseases (MI, congestive HF, stroke, cancer, dementia, death), however, the trial was not yet listed in ClinicalTrials.gov as of May 2020.…”
Section: Sglt2 Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation